Skill Project Module as a Means of Building Morals and Leadership Spirit of Students at Daarul Mutqin Islamic Boarding School, Bogor, West Java - Muhamad As'ad Humam; Siti Mahmudah Noorhayati (Immortalis Journal of Interdisciplinary Studies, 2026)
This study aims to analyze the implementation of the Skill Project Module as a medium for fostering moral character and leadership spirit among students (santri) at Daarul Mutqin Islamic Boarding School, Bogor, West Java. This research is motivated by the need for integrative character education that combines religious values with practical skills and leadership development. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving pesantren leaders, teachers, and students. The findings show that the Skill Project Module effectively supports the formation of moral values such as honesty, responsibility, discipline, cooperation, and independence through structured project-based activities that encourage active participation, teamwork, and problem-solving. In addition, the module strengthens students’ leadership qualities by providing opportunities to manage tasks, make decisions, and reflect on their actions under mentor guidance. This study highlights the importance of project-based skill programs as a strategic instrument for sustainable character and leadership development in Islamic boarding schools.